Mode of First Delivery and Severe Maternal Complications in the Subsequent Pregnancy. Issue 2 (June 2018) - Colmorn, L.B.; Krebs, L.; Klungsøyr, K.; Jakobsson, M.; Tapper, A.M.; Gissler, M.; Lindqvist, P.G.; Källen, K.; Gottvall, K.; Bordahl, P.E.; Bjarnadóttir, R.I.; Langhoff-Roos, J.
Abstract : ( Acta Obstet Gynecol Scand . 2017;96(9):1053–1062) Cesarean delivery rates have been rising worldwide since the 1990s despite well-known long-term maternal risks, including complications in subsequent pregnancies. In Nordic countries, intended vaginal delivery is traditionally the recommended mode of delivery after cesarean. The safety of vaginal delivery after cesarean has been called into question. This study aimed to explore the risks of severe complications at delivery following a first elective or emergency cesarean delivery and the risk of complications by the intended delivery mode.